2014
DOI: 10.1051/fruits/2014003
|View full text |Cite
|
Sign up to set email alerts
|

Main properties of steviol glycosides and their potential in the food industry: a review

Abstract: -Introduction. In recent decades, there has been increased interest in developing natural non-caloric sweeteners, providing sensory properties similar to sucrose. One of the most promising alternatives is the steviol glycosides, high-sweetness compounds extracted from the leaves of Stevia rebaudiana Bertoni. Characteristics and properties. In this review article, the characteristics of this plant are described. According to the relevant literature data, this review provides insight into the major steviol glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…1 Most of them have been known to exhibit high-potency sweetness and low calorific value, which were used commercially as sucrose substitutes. 1 Most of them have been known to exhibit high-potency sweetness and low calorific value, which were used commercially as sucrose substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most of them have been known to exhibit high-potency sweetness and low calorific value, which were used commercially as sucrose substitutes. 1 Most of them have been known to exhibit high-potency sweetness and low calorific value, which were used commercially as sucrose substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Stevia extracts, besides having therapeutic properties, contain a high level of sweetening compounds, known as steviol glycosides, which are thought to possess antioxidant, antimicrobial and antifungal activity. [19,41,55,56]. As González, et al [19] have reported stevioside and rebaudioside A have multiple advantages as dietary supplements.…”
Section: Studies On Safe Consumption Of the Stevia And Its Use By Conmentioning
confidence: 99%
“…[19,41,55,56]. As González, et al [19] have reported stevioside and rebaudioside A have multiple advantages as dietary supplements. They are non-metabolizable (non-caloric) [57][58][59] non acidogenic, and do not cause dental caries [60].…”
Section: Studies On Safe Consumption Of the Stevia And Its Use By Conmentioning
confidence: 99%
See 2 more Smart Citations